2009
DOI: 10.1038/npre.2009.4061.1
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon in Agroforestry Systems: An Unexplored Treasure?

Abstract: Soil organic matter (SOM), which contains more reactive organic carbon (C) than any other single terrestrial pool, plays a major role in determining C storage in ecosystems and regulating atmospheric concentrations of carbon dioxide (CO 2) 1. Agroforestry, the practice of growing trees and crops in interacting combinations on the same unit of land 2 , primarily by resource-poor smallholder farmers in developing countries, is recognized as a strategy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Trees may have a higher potential for SOC sequestration than crop and pasture plant species as trees may be associated with higher proportions of stabilized SOC in deeper mineral soil horizons (Nepstad et al 1994;Jobbágy and Jackson 2000). Trees contribute to more C in the relatively stable silt-+ claysized, i.e., lower than 53 μm diameter, fractions in deeper soil profiles than any other agroforestry species (Nair et al 2009b). Further, in surface soil horizons of intensively managed agricultural landscapes, trees potentially reduce SOC losses by reducing soil erosion (Lal 2005).…”
Section: Effects Of Trees On Soil Organic Carbonmentioning
confidence: 99%
“…Trees may have a higher potential for SOC sequestration than crop and pasture plant species as trees may be associated with higher proportions of stabilized SOC in deeper mineral soil horizons (Nepstad et al 1994;Jobbágy and Jackson 2000). Trees contribute to more C in the relatively stable silt-+ claysized, i.e., lower than 53 μm diameter, fractions in deeper soil profiles than any other agroforestry species (Nair et al 2009b). Further, in surface soil horizons of intensively managed agricultural landscapes, trees potentially reduce SOC losses by reducing soil erosion (Lal 2005).…”
Section: Effects Of Trees On Soil Organic Carbonmentioning
confidence: 99%
“…Organic matter improves the resilience of the soil resource, so that it is more productive for a wider range of crops and other plants. The positive effects of trees on soil carbon (e.g., Beedy et al 2014;Nair 2009), soil water retention capacity (Mafongoya et al 2006), and soil fauna (Mafongoya and Sileshi 2006) are supported by a large body of evidence.…”
Section: Improved Soil Fertilitymentioning
confidence: 98%
“…In the last two to three decades, several land and crop management practices have been advocated to restore soil organic carbon and reduce net emissions of CO 2 from the agricultural systems in the tropics [5,26,27]. Among others, practices that restore soil organic carbon and reduce net emissions of CO 2 include crop rotation, avoiding use of bare fallow, conservation tillage, management of organic inputs such as manure and crop residues, restoration of degraded agricultural lands, water management, and agroforestry (e.g., [28][29][30][31][32][33][34]). Studies demonstrated that smallholder farmers can reduce greenhouse gas emissions and maintain carbon stocks in soil and vegetation at relatively low cost by implementing crop and land management practices (e.g., [27,[35][36][37]).…”
Section: Land and Crop Management Practices For Soil C Sequestrationmentioning
confidence: 99%